Recent Insights Into the Multiple Pathways Driving Non-alcoholic Steatohepatitis-Derived Hepatocellular Carcinoma - Takakura, Kazuki; Oikawa, Tsunekazu; Nakano, Masanori; Saeki, Chisato; Torisu, Yuichi; Kajihara, Mikio; Saruta, Masayuki (Frontiers in Oncology, 2019)
The incidence of metabolic syndrome with fatty liver is spreading on a worldwide scale. Correspondingly, the number of patients with the hepatic phenotype of metabolic syndrome, nonalcoholic fatty liver disease (NAFLD), and in its advanced states, nonalcoholic steatohepatitis (NASH) and the subsequent hepatocellular carcinoma (HCC) derived from NASH (NASH-HCC) is increasing remarkably. A large-scale epidemiological study revealed that obesity can be a risk factor of such cancers as HCC. Moreover, despite the ongoing trends of declining cancer incidence and mortality for most cancer types, HCC has experienced a markedly increased rate of both. Considering the differences in liver-related mortality among NAFLD patients, NASH and NASH-HCC should be included in the objectives of initiatives to manage NAFLD patients and their progression to the advanced stages. Unfortunately, research has yet to make a crucial drug discovery for the effective treatment of NASH and NASH-HCC, although it is urgently needed. The latest widespread concept of the “multiple parallel hits hypothesis”, whereby multiple factors contribute concurrently to disease pathogenesis has led to advances in the elucidation of hepatic and systemic molecular mechanisms driving NASH and the subsequent NASH-HCC progression; the results are not only extensive but promising for therapeutics. Here, we have summarized the myriad landmark discoveries of recent research into the pathogenic processes underlying NASH-HCC development and with the greatest possibility for a new generation of pharmaceutical products for interference and treatment.